STRATEGI SEGMENTATION, ADDITION, DAN REDUCTION DALAM PENERJEMAHAN KALIMAT KOMPLKES ARAB-INDONESIA: ANALISIS BERBASIS KLAUSA PADA TEKS ARAB KONTEMPORER - Muhammad Azwar; Anisa Dwi Nurchayati; Andi Holilulloh (Bahasa dan Sastra Arab, Fakultas Adab dan Humaniora, UIN Sunan Gunung Djati, 2026)
The purpose of this study is to describe the structure of complex sentences in contemporary Arabic texts. Following this description, the study will determine the appropriate translation strategy into Indonesian to produce an acceptable translation in the Indonesian language. This study employs a descriptive qualitative method, utilizing data in the form of complex sentences collected from contemporary Arabic books, particularly those in the fields of politics, thought, and law. The data are analyzed by identifying the structural composition of clauses, including main clauses, subordinate clauses, and coordinative-subordinate relations, then tested through translation strategies; segmentation, addition, and/or reduction as well as shift. The results of this study indicate that the complexity of Arabic sentences, in addition to the length of the structural composition, is also caused by the density of the relations of each clause, the use of ḍamīr mustatir, and the combination of certain syntactic functions within a single sentence. Therefore, an acceptable translation into Indonesian requires breaking down complex structures into simpler ones, without losing their semantic aspects. This research offers novelty both theoretically in the study of Arabic-Indonesian linguistics and translation, as well as in the practice of clause-based translation as an approach to complex Arabic sentences.